Critical Issues in Head and Neck Oncology Key Concepts from the Sixth THNO Meeting (Springer International Publishing, 2018)
This book provides an overview of the latest advances in head and neck cancer using a multidisciplinary approach. Commencing with a discussion of epidemiological and diagnostic aspects, including the role of vaccination and key pathological features, the book then follows by examining the role of oncogenomics, proteomics, next generation sequencing and homologous recombination function in predicting outcomes. The topics are presented by epidemiologists, pathologists and basic scientists with further contributions from medical oncologists, head and neck cancer surgical specialists (ORL /HNS), and radiation oncologists in chapters that discuss therapeutic approaches for oral, oropharyngeal and thyroid cancer. Special topics such as the development of novel staging classifications, optimal larynx preservation approaches for laryngeal and hypopharyngeal cancer, surgical reconstruction, new surgical approaches in oropharynx cancer, potential for treatment de-escalation, systemic therapy in nasopharyngeal cancer and salivary gland tumors and treatment approaches for tumors of unknown primary site are discussed in detail. Finally, the role of immunotherapy in the field is highlighted. The chapters are based on the latest data presented at the 6th Trends in Head and Neck Oncology Conference and reflect the most up-to-date information in the field. They are written by many of the most internationally acclaimed authors in the field and are therefore an excellent source for all those interested or actively working in the field of head and neck cancer.